Case Study : Lemang To'ki / Muhammad Shahril Mohammad Rozlan - Mohammad Rozlan, Muhammad Shahril (2021)
This case study is important to assess the background of the selected company, the analysis of the company as the main case study as well as company problems from all the alternatives that have been provided by management. the method used to study the analysis was through company interviews through phone calls and reviews from people who had already bought and tried such products as well as finding business information from the internet. Based on the findings during a google search, I have chosen a food -based business which is the lemang toki business. For example, in this business they sell various types of food and the most special is lemang. This lemang business was started on a small scale since 2006 by a manager named Mr Mazlan. Since 2010, this business has started to grow and attract locals to taste the delicious lemang produced. In the years that followed, the business continued to grow rapidly to this day. various other types of food are also produced such as grilled chicken, rendang, sour water and various types of products. the estimated collection of lemang toki business in a day reaches RM 50 000.